Pengaruh Belanja Infrastruktur terhadap Pertumbuhan Ekonomi Provinsi Nusa Tenggara Timur - Martin Luter; Irlan Indrocahyo; Islahwani Loka Vita Resti (Department of Development Economics, Universitas Sriwijaya, 2019)
This study investigates the impact of infrastructure spending on economic growth in Nusa Tenggara Timur (NTT). This study uses secondary data from 2010-2017 obtained Direktorat Jenderal Perimbangan Keuangan (DJPK) and Badan Pusat Statistik (BPS). Methods of this study applying panel data analysis to find out the effect of infrastructure spending on NTT’s economic growth. The finding of the study indicates that the road and construction infrastructure spending has a positive and significant effect on economic growth in Nusa Tenggara Timur. Thus, it would be better if government infrastructure spending could be prioritized on road and building construction projects. In addition, spending on other infrastructure such as bridges, water networks, electrical and telephone installations is better governed, so that more effective in increasing NTT's economic growth.